Assessing Storytelling Competencies in Indonesian Elementary Education: A Profile Study of Sixth-Grade Students - Arifin, Moch. Gusnul; Hendratno, Hendratno; Sukartiningsih, Wahyu; Istiq'faroh, Nurul; Purwoko, Budi (Papanda Publisher, 2025)
Storytelling skills are essential components of oral communication that reflect a student’s ability to convey ideas effectively, creatively, and engagingly. This study aimed to identify the initial profile of storytelling skills among sixth-grade students (n=26) at SDN Ploso V/176 in Surabaya. The research employed a qualitative descriptive design using structured observations as the primary method of data collection. Twenty-six students participated as research subjects. The observation instrument assessed five key indicators: fluency in conveying story content, appropriate sentence intonation, facial expression and body movement, speech articulation, and clarity of voice volume. The findings revealed that, overall, the storytelling skills of the students were categorized as